AB0676 Relationship between biological biomarkers and changes in right ventricle that precede pulmonary hypertension in patients with systemic sclerosis. (15th June 2017) - Márquez, V Fernández; Soto, C; Robles, A; Noblejas, A; Mártínez, E; Gúzman, G; Busca, C; Arnalich, F; Ríos, JJ
Abstract : Background: A higher prevalence of Pulmonary Hypertension (HP) has been described in patients with Systemic Sclerosis (ES) diagnosis, so this fact significantly overshadows the prognosis, since it leads to the failure of the right ventricle (RV). In this context, it could be very useful to identify ES patients who are at greater risk of developing PH in the future to make an early diagnosis of this complication, and prescribing an early theraphy to improve their prognosis. Objectives: The purpose of this study is to investigate if certain fibrosis, inflammation and vasculopathy biomarkers could be associated to early functional changes in RV, assessed by echocardiography and cardiac nuclear magnetic resonance (MRI) in ES patients. Methods: A cross-sectional study was performed on a cohort of ES patients diagnosed according to the LeRoy modified criteria, who were being following-up in the Systemic Autoimmune Diseases Unit of the Internal Medicine Service of La Paz Universitary Hospital. Serum levels of inflammation (IL-13, IL-6, TNF alpha), vasculopathy (VEGF), fibrosis biological markers (endoglin, PDRFR, TGFB1, TGFB2, TGFB3) and cardiac biomarkers (NT-proBNP, High sensitivity T troponin) were determinated as well as hemodynamic and cardiac morphological variables, were mesured by transthoracic echocardiography (systolic and diastolic eccentricity index, E/E' ratio, E/A, pulmonary artery systolic pressure, RV thickness) and cardiac MRI (Mean pulmonary artery velocity). We investigated how many patients had these markers elevated and how many of them had hemodynamic and morphological cardiac alterated measurements. Results: Twenty patients with a diagnosis of ES (18 females/2 males) aged between 41 and 77 years, with a mean of 56 years, were included. A control group of 9 patients with similar demographic characteristics was included. ES subjets had higher levels of PDGFR (fibrosis marke) compared to the control group. In addition, in the group of ES patients, two statistically significant associations were observed: troponin T levels (hs-cTnT), endoglin and TGFB2 had higher leves in pacients with a systolic eccentricity index >1; a negative correlation was evidenciated between levels of NT-proBNP and the mean pulmonary artery velocity measurement (VELAP). Conclusions: Hs-cTnT, Endoglin and TGF beta are biomarkers that could appear elevated in patients with systolic eccentricity index >1. NT-proBNP is elevated in patients with decreased VELAP. This study demonstrates the association between certain cardiac biomarkers, fibrosis and vasculopathy peptids and early finding suggesting cardiac remodeling that occurs in some ES patients, which may help to predict the development of PH in those patients. References: Mathai SC, Hassoun PM. N-terminal brain natriuretic peptide in scleroderma-associated pulmonary arterial hypertension. Eur Heart J 2007; 28: 140–141. Jinin M, Makino T, Kahjihara I, et al. Serum levels of soluble vascular endotelial grouth factor receptor-2 in patients with systemic sclerosis. Br. J. Dermatol. 2010; 162: 751–758. Roy AK, McCullagh BN, Segurado R et al. Detection of high-sensitivity troponin in outpatients with stable pulmonary hypertension identifies a subgroup at higher risk of adverse outcomes. J Card Fail 2014; 20 (1): 31–37. Disclosure of Interest: None declared